U Ok Hun?: The digital commodification of white woman style. (2nd April 2022) - Ilbury, Christian
Abstract: Sociolinguistic research has increasingly explored the ways in which semiotic features are variably recruited to stylistically perform enregistered social personae. In this paper, I add to this body of work by exploring the emergence of a stereotypically feminine style and persona that is widespread in British social media. Specifically, I examine the prevalence of non‐standard spellings (e.g., darling, gorgeous ), discourse features (e.g., hun, babe, u ok hun? ), and characterological tropes (e.g., the life motto ' live, love, laugh ') as indexical representations of a particular type of classed, gendered, and ethnic identity in a corpus of Instagram memes. I demonstrate that these features have become enregistered as a characterological figure of a British working‐class White woman—the Hun—that is stylistically deployed as a digital commodity register. Concluding, I emphasise the need for research to engage more fully with stylisation and commodification in social and digital media interaction.